POEMA PEDAGÓGICO: UMA EXPERIÊNCIA EDUCACIONAL INOVADORA, DESENVOLVIDA POR MAKARENKO E SUA RELAÇÃO COM O MARXISMO | Pedagogical Poem: an innovative educational experience, fostered by Makarenko and his affinity with Marxism - Maria Auxiliadora Monteiro de Oliveira; Juliana Cristina Maciel Martins (Trabalho & Educação, 2018)
Antón Semiónovirch Makarenko was born in Bielopie, Krákov, in 1888, and died in 1939. He lived through the Russian Revolution of 1917, in which the Bolsheviks, headed by Lenin, appointed him as leader of the Council of People’s Commissars and overthrew Tsar Nicholas II. In this historical period, Russia faced two hecatombs, namely, World War I and the mentioned Revolution and, consequently, millions of children and, above all, young people engaged in prostitution, theft, and murder, among other felonies. Amidst such context, the educator on the agenda was designated as director of the Gorky Colony, near Poltava. In his mission he was heavily influenced by Lenin, mainly concerning the relevance ascribed to arts, aesthetics, and ethics towards the shaping of a new man who should be inserted in a new